A Novel System for Evaluating the Inhibition Effect of Drugs on Cytochrome P450 Enzymes in vitro Based on Human-Induced Hepatocytes (hiHeps) - Li, Yan; Lu, Ying-Yuan; Jia, Jun; Fang, Meng; Zhao, Lin; Jiang, Yong; Shi, Yan; Tu, Peng-Fei; Guo, Xiao-Yu (Frontiers in Pharmacology, 2021)
Cytochrome P450 (CYP) is the most important phase Ⅰ drug metabolizing enzyme and the effect of drugs on CYP enzymes can lead to decrease pharmacological efficacy or enhance the toxicity of drugs, but there are many deficiencies in the evaluation models of CYP enzymes in vitro. Human induced hepatocytes (hiHeps) derived from human fibroblast by transdifferentiation have mature hepatocyte characteristics. The aim was to establish a novel evaluation system for the effect of drug on CYP3A4, 1A2, 2B6, 2C9 and 2C19 in vitro based on hiHeps. Curcumin can inhibit many CYP enzymes in vitro, and so the inhibition of curcumin on CYP enzymes was compared by human liver microsomes, human hepatocytes and hiHeps using UPLC-MS and cocktail method. The results showed that the IC50 values of CYP enzymes in hiHeps group were similar to that in hepatocytes group, which proved the effectiveness of the novel evaluation system in vitro. Subsequently, the evaluation system was applied to study the inhibitory activity of notoginseng total saponins (NS), safflower total flavonoids (SF) and herb pair of NS–SF on five CYP enzymes. The mechanism of improving efficacy after NS and SF combination based on CYP enzymes was elucidated in vitro. The established evaluation system will become a powerful tool for the research of the effect of drugs on the activity of CYP enzymes in vitro, which has broad application prospects in drug research.